Self Efficacy Selama Pembelajaran Di Masa Pandemi Covid 19 Berdasarkan Gender - Siswanto, Rizki Dwi; Juandi, Dadang; Morin, Shelly; Inayah, Sarah (ANARGYA: Jurnal Ilmiah Pendidikan Matematika, 2022)
This study aims to describe self-efficacy during learning during the Covid-19 pandemic based on gender. Using a non-experimental design with a quantitative descriptive approach. Collecting data using 30 statement questionnaires based on every aspect needed to achieve self-efficacy conditions, namely magnitude, generality, and strength. Subjects amounted to 616 respondents, consisting of students and students from various schools and universities, obtained by random sampling technique. Data analysis uses descriptive statistics, which do not aim to draw conclusions about the entire population but rather help understand the details of the sample. The results of the study concluded that, overall, the average self-efficacy of the respondents was in the moderate category. The magnitude aspect is in the medium category and the other is high. The medium category on the magnitude shows the need for attention to the level of task difficulty, meaning that it describes students and students who will be able to do enough to do tasks that are considered feasible and avoid situations and behaviors that are beyond their capabilities. High category on generality, meaning that students’ beliefs and students to complete the given task can take place in appropriate and real situations and psychology. The high category on strength means that students and students have persistent expectations in trying to complete assignments well, even though they do not have experience. Based on gender, it was found that female and male students had self-efficacy, which tended to be the same in dealing with the dynamics of learning during the COVID-19 pandemic.